Localized synovial sarcoma: A single institutional study of 191 patients with a minimum follow‐up of 5 years for survivors. Issue 7 (20th February 2019) - Outani, Hidetatsu; Nakamura, Tomoki; Murata, Hiroaki; Stevenson, Jonathan; Parry, Michael; Gregory, Jonathan; Tillman, Roger; Jeys, Lee; Abudu, Adesegun
Abstract: Purpose: Factors affecting long‐term outcomes of synovial sarcoma (SS) remain unknown. Here, we aimed to investigate the long‐term oncological outcomes and prognostic factors in a large group of patients with surgically‐treated localized SS. Patients and Methods: Between 1980 and 2011, 191 patients (94 males and 97 females) were treated at a single hospital with a minimum follow‐up of 5 years for survivors. The median age was 35 years (range, 3‐80 years), and the median follow‐up period was 83 months (range, 3‐235 months). Results: Disease‐specific survival was 76.4% and 60.4% at 5 and 10 years, respectively. Local recurrence occurred in 23 patients at a median of 33 months (range, 6‐158 months), and metastasis occurred in 73 patients at a median of 20 months (range, 2‐166 months). In multivariate analysis, grade 3 tumors sized ≥5 cm were significantly associated with worse survival. Ten patients (5.2%) developed metastasis more than 5 years after surgery. Conclusion: Tumor size and grade govern prognosis in surgically‐treated localized SS in long‐term settings. If adequately treated patients have not developed metastases for 5 years after surgery, the risk of subsequently developing metastases was lower than previously reported.